Beneficial effects of autologous mesenchymal stem cell transplantation in active progressive multiple sclerosis - Petrou, Panayiota; Kassis, Ibrahim; Levin, Netta; Paul, Friedemann; Backner, Yael; Benoliel, Tal; Oertel, Frederike Cosima; Scheel, Michael; Hallimi, Michelle; Yaghmour, Nour; Hur, Tamir Ben; Ginzberg, Ariel; et al. (Brain (London, England : 1878), 2020)
In this study (trial registration: NCT02166021), we aimed to evaluate the optimal way of administration, the safety and the clinical efficacy of mesenchymal stem cell (MSC) transplantation in patients with active and progressive multiple sclerosis. Forty-eight patients (28 males and 20 females) with progressive multiple sclerosis (Expanded Disability Status Scale: 3.0-6.5, mean : 5.6 ± 0.8, mean age: 47.5 ± 12.3) and evidence of either clinical worsening or activity during the previous year, were enrolled (between 2015 and 2018). Patients were randomized into three groups and treated intrathecally (IT) or intravenously (IV) with autologous MSCs (1 × 106/kg) or sham injections. After 6 months, half of the patients from the MSC-IT and MSC-IV groups were retreated with MSCs, and the other half with sham injections. Patients initially assigned to sham treatment were divided into two subgroups and treated with either MSC-IT or MSC-IV. The study duration was 14 months. No serious treatment-related safety issues were detected. Significantly fewer patients experienced treatment failure in the MSC-IT and MSC-IV groups compared with those in the sham-treated group (6.7%, 9.7%, and 41.9%, respectively, P = 0.0003 and P = 0.0008). During the 1-year follow-up, 58.6% and 40.6% of patients treated with MSC-IT and MSC-IV, respectively, exhibited no evidence of disease activity compared with 9.7% in the sham-treated group (P < 0.0001 and P < 0.0048, respectively). MSC-IT transplantation induced additional benefits on the relapse rate, on the monthly changes of the T2 lesion load on MRI, and on the timed 25-foot walking test, 9-hole peg test, optical coherence tomography, functional MRI and cognitive tests. Treatment with MSCs was well-tolerated in progressive multiple sclerosis and induced short-term beneficial effects regarding the primary end points, especially in the patients with active disease. The intrathecal administration was more efficacious than the intravenous in several parameters of the disease. A phase III trial is warranted to confirm these findings.